Community Participation in the Application of Educational Policies to Improve Learning Outcomes in Rural Areas - Jailani, Muhammad; Indrojiono, FX.; Anwar, Herson; Irwandi, Irwandi (Asian Journal of Applied Education (AJAE), 2025)
Community participation is essential in improving education quality, particularly in rural areas facing resource and access limitations. This study explores the role and effectiveness of community involvement in implementing education policies to enhance student learning outcomes. A qualitative-descriptive approach was used, involving field observations, policy document analysis, and in-depth interviews with stakeholders in remote areas. Findings indicate that active participation from parents, community leaders, and local organizations supports policy monitoring, informal learning assistance, and a strong learning culture. However, effectiveness depends on policy literacy, local government support, and collaboration frameworks. The study highlights the need to adapt policies to local socio-cultural contexts and develop partnership models to ensure inclusive and sustainable rural education.